Organizational Democracy: Investigating Dimensions, Impact, and Methodology via a Literature Review - Syed Qasim Shah; Suhaimi Mhd Sarif (Journal of Management Practices, Humanities and Social Sciences, 2023)
Organizational democracy, a progressive paradigm shift in workplace dynamics, empowers employees through active involvement in decision-making, transparent communication, and equitable information sharing. This paper offers a comprehensive exploration of organizational democracy's dimensions, strategies for implementation, and its wide-ranging impact on both individual engagement and overall organizational performance. Key insights reveal that embracing organizational democracy leads to heightened employee engagement, increasing innovation and commitment. While challenges like resistance to change are evident, practical recommendations are provided for practitioners, urging leadership endorsement, effective communication strategies, and targeted training initiatives to smooth the transition. Looking ahead, the research highlights the need for cross-cultural analyses and longitudinal investigations to deepen our understanding of how organizational democracy operates in diverse settings over time. This paper underscores organizational democracy's potential to reshape workplaces into thriving hubs of collaboration, creativity, and resilience.